Time for Time: Uncovering Case Processing Duration as a Source of Punitiveness - Liu, Lin (Crime & delinquency, 2022)
The literature on sentencing has devoted ample consideration to how prosecutors and judges incorporate priorities such as retribution and public safety into their decision making, typically using legal and extralegal characteristics as analytic proxies. In contrast, the role of case processing efficiency in determining punishment outcomes has garnered little attention. Using recent data from a large Florida jurisdiction, we examine the influence of case screening and disposition timeliness on sentence outcomes in felony cases. We find that lengthier case processing time is highly and positively associated with punitive outcomes at sentencing. The more time prosecutors spend on a case post-filing, the more likely defendants are to receive custodial sentences and longer sentences. Case screening time, although not affecting the imposition of custodial sentences, is also positively associated with sentence length. These findings are discussed through the lens of instrumental and expressive functions of punishment.